Evaluation of risk factors associated with fragility fractures and recommendations to optimise bone health in children with long-term neurological condition - Xue Yi Jessica Leow; Jonathan Tian Ci Tan; Tong Hong Yeo; Kenneth Pak Leung Wong; Arjandas Mahadev; Bixia Ang; Rashida Farhad Vasanwala; Zhi Min Ng (Singapore Medical Journal)
Introduction: The growing years are paramount for bone growth and mineral accrual. Children with long-term neurological condition (LTNC) have multiple risk factors for poor bone health and fragility fractures. In Singapore, this has not been studied systematically. Therefore, we aimed to evaluate the risk factors associated with fragility fractures in children with LTNC. Methods: In this study, the search for fragility fractures was done by a retrospective review of patients with LTNC on follow-up in the paediatric neurology clinic and patients who presented with fracture to the paediatric orthopaedic clinic. Information on patients’ demographics, medical history, intervention, biochemical bone markers and fracture history was collected. Results: In a tertiary clinic population of 136 patients with LTNC, 65% were dependent on mobility (Gross Motor Function Classification System [GMFCS] V), 60% were underweight and 60% were fed via gastrostomy or nasogastric tube, or were on oral pureed diet. Furthermore, 60% were on anticonvulsants. The fracture rate was 3% in this population and was associated with low-impact activities such as transfer and dressing. Only 7.4% and 33% of the patients had undergone measurements of vitamin D and calcium levels, respectively. Conclusion: The local prevalence of fragility fractures in children with LTNC on follow-up at the neurology clinic was found to be 3%. Risk factors identified were limited ambulation and compromised nutritional status associated with feeding difficulty. Recommendations to optimise bone health in children with LTNC were made. These include promoting weight-bearing activities, looking out for underweight children, avoiding vitamin D deficiency and ensuring adequate calcium intake.